CSR awareness, communication, and trust: how Generation Z shapes ethical consumerism in recovering economies - Papadopoulos, Angelis-Evangelos; Arsenos, Panagiotis; Sykianakis, Nicos; Stavroulakis, Dimitrios (Frontiers in Sustainability, 2025)
BackgroundCorporate Social Responsibility (CSR) has evolved from a peripheral philanthropic activity into a strategic necessity, particularly in recovering economies where social trust and consumer confidence are fragile. Generation Z, shaped by economic turbulence and heightened social awareness, increasingly demands transparency and ethical integrity from corporations. Yet, despite growing CSR awareness, little is known about how communication and trust translate that awareness into ethical consumer behavior in such contexts.ObjectiveThis study aimed to examine how CSR awareness, communication, and trust influence the ethical consumerism of Generation Z in a recovering economy, focusing on the mechanisms through which awareness transforms into loyalty and advocacy.MethodsA quantitative research design was employed using a structured questionnaire administered to 322 Generation Z consumers in Greece. Descriptive and inferential analyses, including exploratory factor analysis and multiple regression models, were conducted to evaluate the relationships among CSR awareness, communication, trust, and ethical purchasing behavior. The study integrated the Theory of Planned Behavior (TPB) and Social Identity Theory (SIT) to interpret how attitudes, social norms, and identity alignment shape consumer choices.ResultsFindings reveal that while CSR awareness among Generation Z is moderate, participation in formal CSR education is low. Despite this limited depth of knowledge, respondents strongly perceive CSR as beneficial to society and the. Regression analyses demonstrate that CSR awareness significantly predicts consumer, while communication positively influences trust and transparency reinforced through NGO partnerships enhances credibility. Simplified CSR messaging also contributes to ethical consumerism by improving comprehension.